2004
DOI: 10.1152/physiolgenomics.00127.2004
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of the dopaminergic system in hypertension

Abstract: Abnormalities in dopamine production and receptor function have been described in human essential hypertension and rodent models of genetic hypertension. Under normal conditions, D 1-like receptors (D1 and D5) inhibit sodium transport in the kidney and intestine. However, in the Dahl salt-sensitive and spontaneously hypertensive rats (SHRs) and in humans with essential hypertension, the D 1-like receptor-mediated inhibition of epithelial sodium transport is impaired because of an uncoupling of the D1-like rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
0
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(183 citation statements)
references
References 227 publications
3
172
0
6
Order By: Relevance
“…Dopaminergic system (DS)/sympathetic nervous system. Dopamine is produced locally in the proximal tubule cells and, after binding to D1 and D5 receptors, inhibits sodium absorption, thereby promoting natriuresis (381). Downstream signaling is mediated through G-protein subunits that are activated by G protein-coupled receptor kinase type 4 (GRK-4).…”
Section: High Saltmentioning
confidence: 99%
“…Dopaminergic system (DS)/sympathetic nervous system. Dopamine is produced locally in the proximal tubule cells and, after binding to D1 and D5 receptors, inhibits sodium absorption, thereby promoting natriuresis (381). Downstream signaling is mediated through G-protein subunits that are activated by G protein-coupled receptor kinase type 4 (GRK-4).…”
Section: High Saltmentioning
confidence: 99%
“…From human and animal studies, there is evidence for a renal dopamine receptor-or better signalling defect-in hypertension. Studies in the D 1 receptor protein, G proteins, adenylyl cyclases, phospholipase C, sodium transporters or the sodium pump revealed no causal abnormalities, so far (for review of the renal dopaminergic system in hypertension see Zeng et al 2004). Since the hypertensive phenotype with respect to renal dopamine signalling resembles processes observed in uncontrolled receptor desensitization, Felder et al (2002) studied D 1 receptor desensitization processes and observed an enhanced phosphorylation of the receptor protein at serine residues, which was attributed to an enhanced activity of the G protein-coupled receptor kinase 4 (GRK4).…”
Section: Genetic Variants Of G Protein-coupled Kinasementioning
confidence: 99%
“…Transgenic mice, overexpressing the GRK4γ isoform with the 142Val variant, exhibited increases in mean blood pressure by ∼30 mmHg compared to mice overexpressing the human wildtype variant . Mice overexpressing the GRK4 486Val variant were initally normotensive but developed hypertension on a sodium diet (Zeng et al 2004).…”
Section: Genetic Variants Of G Protein-coupled Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…One reason for the development and maintenance of this form of hypertension is the reduced capacity of the kidneys to excrete water and salts in appropriate relation to the intake [1]. In parallel with sodium, chloride is reabsorbed as the main accompanying anion and NaCl reabsorption regulation is critical in renal NaCl balance, which in turn controls extracellular volume and blood pressure [2]. About 50-70% of the filtered chloride is reabsorbed in the proximal tubule (PT) [3].…”
Section: Introductionmentioning
confidence: 99%